Assessment of antimicrobial pharmacokinetics curricula across schools and colleges of pharmacy in the United States. Issue 1 (15th October 2021) - Fong, Gary; Chahine, Elias B.; Justo, Julie Ann; Narayanan, Navaneeth; Heil, Emily L.; Stover, Kayla R.; Cho, Jonathan C.; Jenkins, Zachary N.; MacDougall, Conan
Abstract: Introduction: Advances in technology and understanding of pharmacokinetic/pharmacodynamic relationships have prompted guideline updates and advances in precision dosing, but the role of clinical pharmacokinetics (PK) in pharmacy education remains inconsistent. Previous surveys of pharmacy school PK curricula revealed large variations in content, integration, and teaching tools but did not focus on antimicrobials or details of andragogy used. Objective: Identify how antimicrobial PK is taught in pharmacy curricula across the United States, as well as instructor perceptions of current practices. Methods: An online survey was distributed to 118 pharmacy programs across the United States in 2018. This 30‐minute questionnaire covered curriculum content, teaching strategies, assessment modalities, and perceptions. Results: Completed surveys were received from 53 programs (45% response rate) via relevant course coordinators. Among 35 traditional progressive curriculum programs (TPC), antimicrobial PK was taught in basic science (33, 94%), clinical PK (15, 43%), pharmacology (8, 23%), therapeutics (28, 80%), and skills lab courses (21, 65%). Among 18 integrated block curriculum programs (IBC), it was taught in foundations/principles (17, 94%), organ systems (12, 67%), and skills lab courses (9, 50%). On average, TPC programs had more courses with antimicrobial PK than IBC programs. Vancomycin and aminoglycosides were the most common antimicrobials taught (100%), while didactic lecturing was the predominant andragogy. Multiple choice was the primary assessment modality, being frequently used in 64% of TPC and 68% of IBC courses, respectively. Among respondents, 72% believed more time was needed to teach PK and 53% believed students were adequately prepared at the start of APPEs. Conclusion: Antimicrobial PK instruction remains highly inconsistent in U.S. pharmacy schools and colleges. IBC programs may provide less opportunity for antimicrobial PK instruction, which conflicts with the desire for more instruction time. As clinical applications of antimicrobial PK change and expand, it is crucial that pharmacy education prioritizes PK education appropriately.